Laurence Housman papers - Housman, Laurence, 1865-1959.
Correspondence relating chiefly to the life and work of Housman's brother, the English poet A. E. Housman (1859-1936). Correspondents include Seymour Adelman, Witter Bynner, Sydney Carlyle Cockerell, J. M. Edmonds, Andrew Sydenham Farrar Gow, Maude Miller Hawkins, G. Wren Howard, Norman Marlow, Houston Martin, and Grant Richards.
British author.
Collection material in English.
Keywords: Adelman, Seymour, -- 1906- -- Correspondence; Bynner, Witter, -- 1881-1968 -- Correspondence; Cockerell, Sydney Carlyle, -- Sir, -- 1867-1962 -- Correspondence; Edmonds, J. M. -- Correspondence; Gow, Andrew Sydenham Farrar, -- 1886-1978 -- Correspondence; Hawkins, Maude Miller -- Correspondence; Housman, A. E. -- 1859-1936 -- Correspondence; Howard, G. Wren -- 1893-1968 -- Correspondence; Marlow, Norman -- Correspondence; Martin, Houston -- Correspondence; Richards, Grant, -- 1872-1948 -- Correspondence; Classicists -- Great Britain; Poets, English -- 20th century; Authors